PERKEMBANGAN KEBERAGAMAAN MASYARAKAT MINANGKABAU:TINJAUAN SOSIOLOGI SASTRA TERHADAP NOVEL DARI SURAU KE GEREJA KARYA HELMIDJAS HEND - , Nori Anggraini, Prof. Dr. Siti Chamamah Soeratno ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Helmidjas Hendra`s novel Dari Surau Ke Gereja present social phenomena of Minangkabau society, related religious development on Minangkabau society. Based on the background, this research aimed to discover social condition of Minangkabau society presented in novel Dari Surau Ke Gereja. In addition, this research was also to present related philosophy and leadership`s action of Minangkabau cultural in novel Dari Surau Ke Gereja. It was descriptive qualitative research using literary work (novel) as main data. This research used literary sociology theory referring to literature as social reflection of society. Result indicated that there are some factors religious development on Minangkabau society in novel Dari Surau Ke Gereja. The religious development were related to the philosophy âadat bersendikan syara`, syara` bersendikan kitabullaâ and leadership`s action âtungku tiga sejerangan (ninik-mamak, alim ulama, cerdik pandai) not being considered to protect Minangkabau society to keep their religion and tradition as culture`s philosophy. The religious development in Minangkabau cultural in novel Dari Surau Ke Gereja is caused by some factors such as (1) internal`s factor:knowledge, marriage, and economic, (2)eksternal`s factor:others religion mission.